2013
DOI: 10.1136/amiajnl-2012-001208
|View full text |Cite
|
Sign up to set email alerts
|

Patient-generated secure messages and eVisits on a patient portal: are patients at risk?

Abstract: Patients use portal messages 3.5% of the time for potentially high-risk symptoms of chest pain, breathing concerns, abdominal pain, palpitations, lightheadedness, and vomiting. Death, hospitalization, or an ED visit was an infrequent outcome following a secure message or eVisit. Screening the message subject line for high-risk symptoms was not successful in identifying high-risk message content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 14 publications
1
63
0
Order By: Relevance
“…The physicians in this system are not compensated for providing e‐visit access and are expected to respond within 48 h. While we do not analyze the patient characteristics in this study, prior literature shows that e‐visit adopters are more likely to be male, White (as opposed to African‐American or Hispanic), high income, and have more comorbidities (Bavafa et al, ; Yamin et al, ). The most frequently discussed e‐visit topics are medication, lab results, and patient questions about symptoms (Byrne, Elliott, & Firek, ; North et al, ). In our data, physicians start using e‐visits at different points in time, a feature that we leverage in a robustness check using instrumental variable analysis.…”
Section: Empirical Strategymentioning
confidence: 99%
“…The physicians in this system are not compensated for providing e‐visit access and are expected to respond within 48 h. While we do not analyze the patient characteristics in this study, prior literature shows that e‐visit adopters are more likely to be male, White (as opposed to African‐American or Hispanic), high income, and have more comorbidities (Bavafa et al, ; Yamin et al, ). The most frequently discussed e‐visit topics are medication, lab results, and patient questions about symptoms (Byrne, Elliott, & Firek, ; North et al, ). In our data, physicians start using e‐visits at different points in time, a feature that we leverage in a robustness check using instrumental variable analysis.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Together, these limitations could lead to misdiagnosis or poor quality of care. [4][5][6] Although there have been several studies of telemedicine services between primary care providers (PCPs) and their existing patients, 5,7 there has been limited prior work on the quality of DTC telemedicine outside of the medical home and whether DTC telemedicine actually increases access for the underserved. In prior work we have examined antibiotic prescribing in DTC telemedicine 8 but did not look at established quality measures or access to care.…”
Section: Introductionmentioning
confidence: 99%
“…[15, 16] North et al manually classified 323 messages, demonstrating 37% were medication related, 23% were symptom related, 20% were test related, 7% were medical questions, 6% were acknowledgements, and 9% had more than one issue [16]. Haun et al asked senders classify their messages in predefined categories and observed the following distribution, although user-assigned categories were not consistently applied accurately: 59% general (i.e., condition management/report, specialty/procedure request, correspondence request, medication refill request,), 24% appointments (i.e., confirmations, cancellations, specialty appointment requests), and 16% refill and medication inquiries [15].…”
Section: Introductionmentioning
confidence: 99%